Elephants and woodlands - comment by R. du Toit (Co-Editor) - W. Lindsay (Pachyderm)
The letter is intended to further the ongoing discussion focused on issues relating to elephants and woodlands. Management interventions, such as culling have impacts on ecological processes, and should be cautiously applied. The questions of elephant dietary requirements, and the categorization of elephants as primary grazers are addressed. The development of equilibria in interactions between elephants and woody plant communities, and reasons as to why it would be inappropriate to describe elephants as maladapted are discuss.